PEMBUNUHAN DALAM PERSPEKTIF HUKUM ISLAM - Yusuf, Imaning (Universitas Islam Negeri Raden Fatah Palembang, 2013)
Abstract: Killing is a despicable act, sinful, contrary to the objectives of Islamic law. Islam forbids suicide and kills others. In the Qur'an explicitly, explaining that killing is a crime or a criminal offense punishable by Qisas, if it fulfills certain conditions, if the conditions are not met then it will be subject to penalties Diyat.ملخص: قتل هو عمل حقير، خاطئين، يتعارض مع أهداف الشريعة الإسلامية. الإسلام يحرم الانتحار وقتل الآخرين. في القرآن صراحة، موضحا أن القتل هو جريمة أو جريمة جنائية يعاقب عليها القصاص، إذا كان يلبي شروط معينة، إذا لم يتم استيفاء الشروط وبعد ذلك سوف تكون خاضعة لعقوبات الديةKata kunci: hukum islam, qisas, diyat.